Friend or Foe? The Ambiguous Role of Innate Lymphoid Cells in Cancer Development - Mattner, Jochen; Wirtz, Stefan (Trends in Immunology, 2017)
The development of immunotherapies represents a major advance towards the effective eradication of malignant tumors. So far, therapeutic approaches have largely focused on T lymphocytes, but the innate arm of the immune system might be similarly important. Innate lymphoid cells (ILCs) are rapidly-responding cells that are functionally analogous to diverse T cell subsets. In recent years these cells have attracted enormous attention owing to their pleiotropic effects in early host defense to infection and organ pathologies. ILCs might also represent promising targets in the context of cancer therapy because they are an innate immune cell population endowed with potent immunomodulatory properties. In this review we discuss the impact of the three ILC subsets and the signature cytokines they release on cancer development and tumor growth.
EVALuna2:7741